The Association Between Female Smoking and Childhood Asthma Prevalence–A Study Based on Aggregative Data - Midya, Vishal; Pal, Shekhar; Sinharoy, Ankita; Das, Jishu K.; Rao, Harish; Abu-Hasan, Mutasim; Mondal, Pritish (Frontiers in Public Health, 2018)
Aims: Socioeconomic and environmental factors influence childhood asthma prevalence across the world. In-depth epidemiological research is necessary to determine the association between asthma prevalence and socio-environmental conditions, and to develop public health strategies to protect the asthmatic children against the environmental precipitators. Our research was based on aggregative data and sought to compare the asthma prevalence between children of two different age groups across the world and to identify the association among the key socio-environmental conditions with increased childhood asthma prevalence. Method: We included forty countries with available data on various socioeconomic and environmental conditions (2014-2015). Childhood asthma prevalence of two different age-groups (6-7 years and 13-14 years) were obtained from global asthma network report 2014. Because of significant diversities, the selected countries were divided into two groups based on human developmental index (HDI), a well-recognized parameter to estimate the overall socioeconomic status of a country. Robust linear regression was conducted using childhood asthma prevalence as the dependent variable and female smoking prevalence, tertiary school enrollment (TSE), PM10 (particulate matter ≤10 µm in diameter) and gross domestic product (GDP) as predictors. Results: Asthma prevalence was not different between two age groups. Among all predictors, only female smoking prevalence was associated with asthma prevalence in the countries with lower socio-economic conditions (HDI), but not in the higher HDI group. The results were unchanged even after randomization. Conclusions: Childhood asthma prevalence did not change significantly with age. Female smoking may have a positive correlation with childhood asthma prevalence in lower HDI countries.